Ayurvedic Management of Schizophreniform Disorder (AYUSHDHARA, 2024)
Schizophreniform disorder shares characteristic symptoms identical to that of schizophrenia, but is distinguished by its difference in duration. An 18-year-old male patient was admitted in the Government Ayurveda Research Institute for Mental Health and Hygiene, Kottakkal, with increased fear, reduced sleep and food intake, not mingling to other people for the past one month. In Ayurveda the psychotic features are enlisted under the term Unmada. Unmada is defined as perversion in Manas, Budhi, Samjnajnana, Smruthi, Bhakthi, Seela, Cheshta and Achara. Management of Unmada is done based on the predominance of Dosha involved in the pathogenesis. Sodhana, Samana and Satwavajaya are included in the management of Unmada. The patient was treated on an IP level with a combination of Ayurvedic internal medications and procedures for 45 days. The treatment protocol including Thalapothicil, Snehapana, Virechana, Vasti, Kashaya dhara, Nasya and Anjana were administered. PANSS was used to evaluate the symptoms before and after the treatment. There was a significant reduction in score from 86 to 30 after the intervention with improvement in the condition and insight. This case report shows the importance of the effective management of Schizophreniform disorder with Ayurvedic treatment procedures and medicines.